Glutathione deficiency and heart failure: a systematic review of human and animal evidence - Ali A. Al-Mubarak; Antonio Esquivel-Gaytan; Herman H.W. Silljé; Peter van der Meer; Nils Bomer (Advances in Redox Research)
Background: Oxidative stress is an important factor underlying several pathophysiological mechanisms in heart failure (HF). Nevertheless, modulating oxidative stress is still a significant challenge due to the lack of specific and modifiable targets. A central component that is integrated into several processes is glutathione, an essential thiol-based compound that is integrated into redox homeostasis. Objective: To establish the significance of glutathione and its availability in relation to HF. Methods: A comprehensive search strategy using PubMed, Embase, and Web of Science was developed. All human studies with patients with HF and animal studies with evidence of significant cardiac remodelling and available measurements of glutathione were included. Results: A total of 7656 articles were initially identified. Following first screening, 426 articles were selected for full assessment, out of which 217 reports were ultimately included in the analysis. There were 21 studies out of 25 that showed lower glutathione measures in patients with HF compared to controls, of which 18 reached statistical significance with an average reduction of 27.8 %. Regarding the animal evidence, 74.2 % and 79.3 % of the measurements in ischemic cardiomyopathy models and models with transverse aortic constriction, showed lower glutathione concentrations as compared to sham groups, respectively. Factors that positively influenced glutathione concentrations included all guideline-directed medical therapies, selenium, amlodipine, and N-acetylcysteine. Conclusion: Glutathione deficiency is a common finding in the context of HF. As it is a measurable and modifiable component with various biological targets, investigating the effects of optimizing its concentration in patients with HF should be pursued.